The Application of Restorative Justice in Violence Against Children in Schools Cimarga Banten - Safitri, Dwi Mulya; Soekorini, Noenik; Aranggraeni, Renda; Borman, Syahrul; Marwiyah, Siti (International Journal of Business, Law, and Education, 2026)
This study analyzes the gap between normative recognition and operational implementation of restorative justice in addressing violence against children in Indonesian educational settings. It focuses on three issues: the legal position of restorative justice, its application in the SMAN 1 Cimarga case, and the need for normative reconstruction to ensure legal certainty and child protection. Using a normative legal approach with statutory, case, conceptual, and comparative analyses, the study finds that although restorative justice is supported by Law No. 11 of 2012 and Law No. 35 of 2014, its implementation remains weak. Institutional barriers include fragmented regulations, lack of clear procedures, and ambiguous authority. The Cimarga case reflects a dominant retributive approach that neglects dialogue and victim recovery. The study concludes that reconstruction is required through integrated regulation, school-based mechanisms, and stronger institutional accountability, including regulatory revision, restorative units in schools, and improved inter-agency coordination.